Absolute density measurements for standard sea-water by hydrostatic weighing of silicon sinker. (December 2021) - Kayukawa, Yohei; Uchida, Hiroshi
Abstract: To evaluate and improve the accuracy of the ther-modynamic equation of state for sea-water (TEOS-10), there are pressing needs for precise density measurements for stan-dard sea-water samples. In the present study, a hydrostatic weighing apparatus using a silicon single-crystal sinker was developed. The relative expanded uncertainty of the density measurement is 1.4 ppm which is the highest among the exist-ing density measurement equipment. The validity of the den-sity measurement was checked by measuring n -tridecane and pure water. Measurement results for standard sea-water sam-ples are discussed in this paper.